2010
DOI: 10.1258/la.2010.009128
|View full text |Cite
|
Sign up to set email alerts
|

Establishing normal plasma and 24-hour urinary biochemistry ranges in C3H, BALB/c and C57BL/6J mice following acclimatization in metabolic cages

Abstract: Physiological studies of mice are facilitated by normal plasma and 24-hour urinary reference ranges, but variability of these parameters may increase due to stress that is induced by housing in metabolic cages. We assessed daily weight, food and water intake, urine volume and final day measurements of the following: plasma sodium, potassium, chloride, urea, creatinine, calcium, phosphate, alkaline phosphatase, albumin, cholesterol and glucose; and urinary sodium, potassium, calcium, phosphate, glucose and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 19 publications
3
57
2
Order By: Relevance
“…Ex vivo analysis of different organs demonstrated that the ab-tMUC1-NIR-MSN nanoprobe is mainly localized in the liver. Interestingly, with comparable values to those observed in normal mice, 59, 60 liver panels conducted in the animals did not show major short-term toxicity due to the presence of the ab-tMUC1-NIR-MSN probe in this organ (Table II). However, additional studies need to be conducted to evaluate the long-term toxicity of the ab-tMUC1-NIR-MSN nanoprobe.…”
Section: Discussionsupporting
confidence: 72%
“…Ex vivo analysis of different organs demonstrated that the ab-tMUC1-NIR-MSN nanoprobe is mainly localized in the liver. Interestingly, with comparable values to those observed in normal mice, 59, 60 liver panels conducted in the animals did not show major short-term toxicity due to the presence of the ab-tMUC1-NIR-MSN probe in this organ (Table II). However, additional studies need to be conducted to evaluate the long-term toxicity of the ab-tMUC1-NIR-MSN nanoprobe.…”
Section: Discussionsupporting
confidence: 72%
“…In naive immunocompetent BALB/c mice, blood chemistry analysis showed no substantial liver or kidney toxicities at this dose, and unchanged immunoglobulin E levels suggested no allergic response to repeated (q4dx4) Pd-NP administration compared to the Pd-free PLGA-PEG NP vehicle control (Supplementary Table 1). ALP decreased slightly (Supplementary Table 1), possibly related to artefactual haemolysis noted in some samples31, but nevertheless remained within a normal physiological range3233. Repeated Pd-NP treatment also yielded no substantial changes in complete blood counts using the fibrosarcoma xenograft model (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…Trpv5 682P/682P mice, were found to be viable, fertile and morphologically indistinguishable from their Trpv5 +/+ and Trpv5 682P/+ littermates. Mice between 12–20 weeks of age were housed in metabolic cages for 24 hours and urine samples collected for biochemical analysis [26]. Trpv5 682P/682P mice were polydypsic and polyuric compared to Trpv5 +/+ mice (p<0.02, Table 1).…”
Section: Resultsmentioning
confidence: 99%